Development of efficient adsorbent materials for removal of toxic substances from water - Song, Xiang Hua (2013)
Water contamination by chemicals such as metal ions and dyes is a serious environmental issue globally. One of the most promising solutions to solve such a problem is the use of adsorption technology. In recent years, the development of efficient and environmentally benign adsorbents using precursors of biopolymer, biomasses, and industrial wastes, etc, has attracted particular research attentions, due to the concerns of economics, environment, and sustainability. In this thesis work, efficient adsorbents as promising alternatives for commercial activated carbons were developed and their adsorption properties were investigated for applications in water treatment. In particular, a series of projects were carried out and important findings are summarized as follows. In the first project, high quality mesoporous activated carbon with surface area of ~1,100 m2/g was derived from waste tyres via the developed steam activation and acid washing protocol. Due to its specific mesoporous structure texture with volume fraction of mesopore (2 - 50 nm) > 70 %, it presents excellent sorption capacities towards basic dye, higher than that of commercial activated carbons. The optimization of synthesis parameters, batch sorption equilibrium, kinetics and mechanisms have been studied and discussed. In the second project, zeolite templated activated carbons (ZTC) with tailored pore size distribution were prepared by the chemical vapor deposition (CVD) method using zeolite NaY as the template and benzene as the carbon precursor. It was found that the CVD temperature of 650 °C results in carbons with the highest surface area of 1,511 m2/g, and a good structural periodicity. The Ag(I) adsorption performance of the ZTC was studied. Besides porous carbon materials, nonporous colloidal carbon nanospheres (CNS) with rich surface functional groups were prepared from glucose solution for adsorption of pollutants from aqueous solutions. The surface of the nonporous CNS after being activated by NaOH was enriched with -OH and -COO functional groups. Despite the low surface area (< 15 m2/g), the activated CNS exhibited excellent adsorption performance toward basic dyes and Ag(I). The adsorption rate is fast, all MB with concentration of 94 ppm, and all Ag(I) with concentrations lower than 2 ppm, can be completely adsorbed in less than 6 minutes. This can be attributed to the minimum mass transfer resistance of the nonporous structure and the rich surface functional groups. Ag(I) ions were all deposited and reduced as Ag0 nanoparticles on the external surface of CNS. The pollutants spent CNS can be easily and efficiently regenerated for recycling runs. For example, the dye spent CNS adsorbents have been regenerated using the sulphate radial based oxidation method and recycled for many adsorption runs with retained capacity. The adsorbed silver can be easily and fast recovered by dilute acid solutions and the CNS can be reactivated with a NaOH solution. The NaOH activated CNS reported here could represent a new type of low- cost and efficient adsorbent nanomaterials for pollutants removal of from wastewater. Lastly, biosorbent of molecular imprinted chitosan (CS) hydrogel beads were prepared to enhance the Ag(I) sorption selectivity and to solve the shortage of decreased adsorption capacity after chemical crosslinking of chitosan beads. The imprinted beads with optimal imprinting ratio show a higher adsorption affinity to Ag(I) under Ag(I)/Cu(II) competitive adsorption conditions, the Ag(I) adsorption rate is faster and Cu(II) adsorption rate is much slower as compared with that of non- imprinted beads. The adsorbed Ag(I) can be easily desorbed from the biosorbent using diluted HNO3 solution. The materials and methods developed in this thesis work are believed to provide promising solutions for efficient removal of metal ions and organic dyes from wastewater.